Epistaxis: the cause found beyond the nose - Rahul Verma; Vinay Nagaraja Gowda; Ashok Singh; Madhu Priya; Sanjeev Kishore; Prashant Pranesh Joshi (University of São Paulo, 2021)
Renal cell carcinoma (RCC) is a malignant disease that is often diagnosed at a metastatic stage. The head and neck represent up to 3% of the metastatic RCC, and the paranasal sinus area is one of the least involved sites. Here, we introduce the case of a 74-year-old female patient who presented with a history of traumatic nasal bleed. A cranial computed tomography scan and magnetic resonance imaging showed a fronto-ethmoidal mass with pachymeningeal involvement. A nasal biopsy from the paranasal sinuses was taken. On histopathological examination, metastatic clear cell carcinoma was the main hypothesis, which later was confirmed to be RCC on immunohistochemistry. On further radiological examination, an exophytic mass was depicted in the kidney's upper and middle pole. The patient had no renal complaints and was asymptomatic. Fronto-ethmoidal sinus is a rare site for metastatic RCC, especially in cases where the patient is asymptomatic. Early detection by keeping RCC metastasis as the differential diagnosis in such cases can lead to early treatment and improve the overall survival of the patient.